Pericardial closure with expanded polytetrafluoroethylene patch in left ventricular assist device surgery - Meinert, Étienne Fasolt Richard Corvin; Kremer, Jamila; Tochtermann, Ursula; Sommer, Wiebke; Warnecke, Gregor; Karck, Matthias; Meyer, Anna L. (ASAIO journal, 2024)
To reduce adhesions after left ventricular assist device (LVAD) implantation, pericardial closure using an expanded polytetrafluoroethylene (ePTFE) patch has been suggested. However, as foreign material, ePTFE patches could increase the risk of infectious complications. In this single-center retrospective study, we investigated outcomes of pericardial closure using an ePTFE patch in LVAD implantation. We included all patients who underwent LVAD implantation at our center between 2011 and 2020 (n = 166). Primary endpoint was development of mediastinitis at any point of time between LVAD implantation and heart transplantation (HTx) or death. Secondary endpoint was overall survival. Preoperative and postoperative clinical data were collected to ensure comparability between the groups. We included 166 patients with LVAD. A total of 116 patients (70%) underwent pericardial closure using an ePTFE patch. There were significant differences between the groups in treatment setting, previous cardiac surgery, Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) level, development of driveline infection, and HTx. Patients with an ePTFE patch developed mediastinitis more frequently (16%) than patients without ePTFE patch (4%) (p = 0.039). A significant difference in overall survival between the groups could not be confirmed (p = 0.29). The use of PTFE patches for pericardial closure in LVAD implantation was associated with a higher incidence of mediastinitis, but not with a difference in overall survival.
Gesehen am 25.11.2024